PROMINENT LEADERSHIP THEORIES AND STYLES: WITH CONTEXT TO HIGHER EDUCATIONAL INSTITUTIONS - Tiwari, Geetanjali; Singh, Vinay Pal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education in general but particularly higher education is always in the state of constant change because of such factors like technology, globalization, and social demands. Thus, one could assert that leadership has emerged as a critical process within the context of higher education owing to the noted developments. In such organizations, corruption of leadership has received a lot of attention as a powerful paradigm that fosters innovation and change. Organizational transformation aims to improve the work done constantly and align people with distinctive goals, stressing the importance of motivating people to achieve high aims. It is particularly relevant in the tertiary level of schooling because in order to undergo long term development a new technology and a change in learning paradigms must occur in the class. The following leadership strategy is defined by creating a visionary plan for the institution’s future and engaging individuals in genuine dialogue. It empowers academic leaders in the position to promote change within their faculties and staffs, which raises the culture of sustainable development and stabilizes the environment for academics. The present scholarly investigation is aimed at discussing leadership characteristics for higher education institutions, their consequences for function and quality, and the best suitable theories and practices for academic environment. In order to ensure the quality of the manpower and its further development, the institutions themselves should pay great attention to formation and further development of strong leadership.